Kashmir's Right to Secede : a Critical Examination of Contemporary Theories of Secession. - Webb, Matthew J. (Routledge contemporary South Asia series., 2012)
A separatist conflict has been ongoing in India-administered Kashmir since 1989. Focusing on this region, this book critiques the existing normative theories of secession, and offers a comprehensive examination of the right of sub-groups to secede. The book looks at the different accounts of the moral right to secede, and assesses both the theories themselves as well as the claims of those who want to separate Kashmir from India. Included within this analysis are the three main types of normative theory that ground the right of groups to secede in principles of national self: determination, co.